Preparation and Characterization of New Heterocyclic Derivatives, Six and Five Ring from Acetanilide - Zainab Amer Sallal , (University of Thi-Qar Journal of Science, 2020)
The aim of the study synthesis of new heterocyclic derivatives (six and five ring) from acetanilide. Firstly the chalcones have been synthesized from the reaction acetanilide with aromatic aldehyde [ 2-nitrobenzaldyhade, 4- dimethylaminobenzaldehyde, 2-naphthaldehyde ] in dilute solution of ethanolic sodium hydroxide at room temperature. This reaction occurs depending on Claisen Schmidt condensation, then a new oxazine and thiazine derivatives (six ring) have been synthesized by the reaction chalcones with urea and thiourea. Finally the synthesized chalcones were reacted with hydrazine hydrate to produce new pyrazol derivatives (five ring). All derivatives were characterized by physical properties, FTIR, 1H-NMR and 13C-NMR spectra.